Antología de jóvenes poetas mexicanos - Frías, José D.
Antología de poetas mexicanos que incluye a Ramón López Velarde, Alfonso Reyes, José de J. Nuñez y Domínguez, José D. Frías, Carlos Roel, Samuel Ruiz Cabañas, Francisco González Guerrero, Enrique Carniado, Humberto Esquivel Medina, Carlos Pellicer, Jaime Torres Bodet, Gregorio López y Fuentes, Enrique Fernández Ledesma, Luciano Joublanc Rivas, Alfonso Junco, Rodrigo Torres Hernández, J. Rubén Romero, Pedro Requena Legarreta, Miguel D. Martínez Rendón, Rafael Lozano, José Antonio Muñoz, Martín Gómez Palacio, José Gorostiza Alcalá, Alfredo Ortiz Vidales y Fernando Ortiz de Montellano.